Evaluation of dispersion behaviour of horizontal water jet by using flow visualization method - Shun WATANABE; Tomohisa YUASA; Ryo MORITA (Nihon Kikai Gakkai ronbunshu, 2020)
This paper presents a detailed experimental study on the dispersion behaviour of a horizontal water jet with atomization. The study mainly focuses on flow structure of the water jet such as a spread angle and a flying distance. The experiments were conducted by using a flow visualization method. Dimensionless numbers (Reynolds number and Weber number) were introduced to determine evaluation condition on a map of the jet flow pattern. The experimental results were compared with existing theoretical model. The jet spread angle was increased by the atomization at the interface between the water jet and surrounding air, and its angle were correlated with non-dimensional numbers. It was also found that the experimental data of the jet flying distance agree with the theoretical model under the low velocity condition. However, the experimental data showed shorter flying distance compared with the theoretical model due to the atomization under the high velocity condition.